(untitled) (Geologica Macedonica, 2013)
The aim of this paper is to define the metamorphism of the skarn rocks from the Sasa ore filed. Inthese rocks ilvaite, rhodonite, bustamite, johansenite-ferrojohansenite, andradite, actinolite-ferroactinolite and epidotewere determined. On the base of the presence minerals associations in studied rocks were determinated three facies:albite-epidote-hornfels facies; hornblende-hornfels facies; K-feldspate-cordierite-hornfels facies. The rocks studiedare formed in temperature condition T 400–800oC and preassure P 1.5–2 kbar.